Основы рационального питания спортсменов - Balash A. E., Khusainov A. V. (Modern education development theory techniques and practice, 2016)
The health, mood and health of the person depends on numerous conditions. To too time from among these conditions characterizing a state of health of the person an essential role it is sent to food. The healthy or balanced diet is a pledge not only health of the person, but also his emotional state. At a balanced diet the human body receives necessary substances for implementation of the majority of vital signs, strengthening of health and to endurance increase that is very important for athlete
Keywords: питание; спортсмены; рацион; athletes; food; diet